Metallothionein isoform 1 and 2 gene expression in the human bladder: evidence for upregulation of MT-1X mRNA in bladder cancer - Somji, S; Sens, M A; Lamm, D L; Garrett, S H; Sens, D A (Cancer detection and prevention, 2001)
The goals of this study were to determine the expression of metallothionein isoform 1 and 2 proteins (MT-1 and MT-2) in bladder cancer and then to determine which MT isoform-specific genes promoted the expression of these proteins. Immunohistochemical analysis disclosed no immunoreactivity for MT-1 and MT-2 (designated as MT-1/2 to reflect the nonspecificity of the antibody for the two isoforms) in cells comprising the normal bladder or in nonmalignant bladder disorders, such as cystitis and interstitial cystitis. Immunohistochemical analysis demonstrated that MT-1/2 was overexpressed in all samples of carcinoma in situ and in high-grade bladder cancer, with variable overexpression in low-grade bladder cancer and dysplastic lesions. The intensity and frequency of MT-1/2 staining correlated with the grade of the tumor. The MT-1 and MT-2 proteins are encoded by a family of eight genes (MT-1A, MT-1B, MT-1E, MT-1F, MT-1G, MT-IH, MT-1X, and MT-2A), and reverse transcriptase-polymerase chain reaction was used to determine which genes were expressed in the normal bladder and in bladder cancer. This analysis demonstrated that both normal and cancerous bladder tissue expressed mRNA for the MT-2A and MT-1X genes. The expression of MT-1E mRNA was variable in both normal bladder and bladder cancer specimens. Comparison of expression relative to that of beta-actin demonstrated that the level of MT-1X mRNA was overexpressed greatly in bladder cancer as compared to the level in normal bladder tissue. In contrast, the level of MT-2A mRNA was similar in both the normal and the bladder cancer specimens. The level of MT-1X expression did not vary with tumor grade. These studies suggest that the overexpression of MT-1/2 protein in bladder cancer is a result of the overexpression of the MT-1X gene.